Percepción estudiantil sobre el uso de una plataforma colaborativa de realidad virtual en el aprendizaje de asignaturas de ciencias - Zuñe Chero, Limberg (2023)
The objective of this study is to explore the perceptions of university students regarding the use of Second Life as a collaborative virtual reality platform for learning science subjects. A cross-sectional non-experimental descriptive analytical empirical research design was employed, utilizing quantitative techniques to gather data from 123 students regarding their experiences with immersion. The results reveal that students exhibited genuine engagement with the virtual environment, displaying high levels of interaction and motivation, which in turn increased their level of participation in immersive activities. These findings suggest that incorporating science content into a virtual world offers diverse didactic possibilities and encourages new forms of engagement among participants in educational processes. The study highlights the potential of virtual reality for enhancing higher education practices.